SEROPREVALENCE OF Coxiella Burnetii AMONG MEAT HANDLERS IN DUHOK CITY, IRAQ. - BAHDEEN JALAL*, RAND; YAHYA SAEED, ALI (Journal of Duhok University, 2019)
Background: Q fever is a zoonotic disease caused by Coxiella burnetii, most commonly infect people who work in close contact with animals and their carcasses like butchers and abattoir workers.Objective: This study was carried out for the first time in the area to show the prevalence of Q fever among butchers and abattoir workers in Duhok city, as one of the main risk groups.Methods: A total of 86 serum samples were collected from butchers (54) and abattoir workers (32) working in Duhok city from June to August, 2018. ELISA kit (Vircell SL, Spain) was used to detect IgG and IgM antibodies against C. burnetii phase II antigen. Results: Out of 86 serum samples with mean age 31.8 ±11.8, 23 (26 %) were positive for IgG in which 12 (22.2%) were butchers and 11 (34.4%) were abattoir workers, while 5 (5.8%) were positive for IgM and only recorded among butchers. The percentages of IgM positive cases were decreased with increasing of age in opposite of IgG cases in which the highest percentage of IgG was 30.2% in age group 16-30 years while the lowest percentage was 16.7% in age group more than 45 years. The same picture was found with years of occupation in which the highest percentage of IgG was 31.8% in those worked from 0.5 to 10 years, while the lowest percentage was 11.8% in those who have more than 20 years of working.Conclusion: Based on the results of this study, it can be concluded that C. burnetii infection is widespread among butchers and abattoir workers.